Investigation of the Association Between Dopamine D1 Receptor Gene Polymorphisms and Essential Hypertension in a Group of Turkish Subjects - FAK, ALİ SERDAR; NACAR, CEVDET; CABADAK, HÜLYA; ORUN, OYA; MEGA TİBER, PINAR (INFORMA HEALTHCARE, 2011)
Dopamine has been shown to influence blood pressure by regulating renal sodium excretion through direct interaction with the dopamine receptors, especially with the Dopamine D1 receptor (DRD1). To better understand the role of polymorphisms in those effects, we investigated the association between two polymorphic sites in the DRD1 promoter region (A-48G, G-94A) and essential hypertension in the Turkish population. The DRD1 variants were genotyped by restriction fragment length polymorphism (RFLP) analysis. A total of 205 unrelated individuals were enrolled in the study. We found that genotype distributions and allele frequencies of the control and hypertensive subjects were very similar and did not show any significant difference with respect to blood pressure (BP) and hypertension. Contribution of the gene variances in BP or hypertension by sex differences and dependence on body mass index (BMI) were also evaluated. Distribution of genotypes and allele frequencies were found to be in line with previous reports. However, increments detected in hypertensive subjects were far from being statistically significant.
Keywords: dopamine; essential hypertension; polymorphism; receptors; DRD1